Mattaresse’ Tradition For Pregnant women in Saotengnga Village, Sinjai Regency, South Sulawesi - Rusli, Rusli; Rahman, Abdul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Mattaresse' is a tradition carried out by the people of Saotengnga Village, Sinjai Regency. This tradition is a hereditary tradition handed down by previous ancestors. This research is a qualitative research that uses an ethnographic approach, the method used by researchers in compiling this journal is a method of observing traditions related to the community in that location, conducting interviews to strengthen and clarify the results of research for the owners of this culture. This tradition is a living and preserved tradition in the local community because it has an important symbolic meaning for those who believe in and carry out the ritual. The purpose of this study was to determine the function, meaning contained in the values of the rituals performed. Mattaresse'/ makkatenni sanro (holding a dukun) is a ritual performed by the local community, especially for pregnant women, what is unique in this culture is that not all Mattaresse' rituals are performed on pregnant women, according to this belief Mattaresse' is only performed for pregnant women who are pregnant. first and the gestational age has reached seven months according to the beliefs of the owner of this culture. Mixing or acculturation between local culture and the beliefs of Islamic teachings because of the mutual influence, adaptation or adjustment of local traditions with Islamic teachings. The renewal between local traditions and Islamic teachings becomes a unity. Although carried out by some Muslims, this tradition is not an Islamic tradition but a Bugis community tradition. This tradition is called Mattaresse 'or seven months.